Publication of Arbitral Awards in Commercial Arbitration: Ordering the Discussion - Zamora Etcharren, Rodrigo (2020)
In recent years, the discussion regarding the publication of arbitral awards has been developing with several arguments being made for and against this type of measures. Multiple arbitration centers have adopted regulations about the subject in their latest rules. However, we still cannot determine which route commercial arbitration will follow when in regards to this matter. In the following article, the authors evidence the multifaceted character of the discussion about the publication of arbitral awards in commercial arbitration. First, they present the regulations that the ten most relevant arbitration centers have adopted in regards to this subject. Then, they explain the characteristics of default rules and the consequences these can have depending on whether they are opt-in or opt-out. Finally, they explore the arguments in favor and in opposition to the publication of arbitral awards.